2018
DOI: 10.1055/a-0586-8255
|View full text |Cite|
|
Sign up to set email alerts
|

Morbidität durch Hitze – eine Analyse der Krankenhauseinweisungen per Rettungseinsatz während einer Hitzewelle 2015 in Frankfurt/Main

Abstract: Heatwaves are gaining in importance due to increasing climatic changes. They can impair health and increase mortality. A comparison of studies is difficult because of differences in the definition of a heatwave used and/or different populations studied. In this study, morbidity data were collected using the web-based IVENA system. This system registers hospital admissions with diagnosis by the emergency medical services. We analysed hospital admissions in Frankfurt/Main during June-August of 2014-2016. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Between 2000 and 2015, roughly 39,000 heat-related excess death cases had been estimated for Germany [30]. Heat-induced morbidity cases might even be higher, as a few local studies have indicated [31,32]. Due to evident heat-related health impacts and a few more effects of other expanding weather extremes, like droughts, heavy storms, and rain, climate-change-related health issues became more and more prominent in the society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2000 and 2015, roughly 39,000 heat-related excess death cases had been estimated for Germany [30]. Heat-induced morbidity cases might even be higher, as a few local studies have indicated [31,32]. Due to evident heat-related health impacts and a few more effects of other expanding weather extremes, like droughts, heavy storms, and rain, climate-change-related health issues became more and more prominent in the society.…”
Section: Discussionmentioning
confidence: 99%
“…The number of hospital admissions increased in July 2015 by 22%, respectively admissions of heat symptom diagnosis, such as heat exhausts, syncope or exsiccosis above 100%. The assessment of this noticeable long-lasting 2018 summer heat showed that an increasing duration of this extreme heat period triggered rising emergency rescue service operations due to total heat associated morbidity remained high with increased cases of exsiccosis and unclear fever [31,32].…”
Section: Heat-related Health Impacts-a New Emerging Issue For Public ...mentioning
confidence: 99%
“…Die Auswirkungen von Hitzeperioden auf die menschliche Gesundheit sind gut dokumentiert [2,3]. Deswegen ist auch die Gefahr übermäßiger Aufheizung von Innenräumen mit entsprechenden Folgen für die Innenraumluftqualität und das Wohlbefinden ein wichtiger Faktor in der öffentlichen Diskussion.…”
Section: Einfluss Des Außentemperaturanstiegs Auf Innenraumklima Und unclassified
“…Aber nicht nur die erhöhte Zahl von Sterbefällen ist mit extre mer Hitzebelastung assoziiert. Auch weitere Gesundheits indikatoren verdeutlichen die besondere Belastungssituation während Hitzeereignissen, wie zum Beispiel eine nachweislich erhöhte Anzahl von Rettungs diensteinsätzen (Bassil et al 2009;Steul et al 2018) oder vermehrte Krankenhausein weisungen (Scherber et al 2014). Darüber hi naus muss davon ausgegangen werden, dass Hitzeereignisse mit weiteren gesundheitlich beeinträchtigenden Umweltbelastungen korrelieren können (Mücke, Matzarakis 2017).…”
Section: Aktuelle Entwicklungunclassified